2006
DOI: 10.1103/physrevlett.96.246804
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Shot Noise in Tunneling through a Stack of Coupled Quantum Dots

Abstract: We have investigated the noise properties of the tunneling current through vertically coupled self-assembled InAs quantum dots. We observe super-Poissonian shot noise at low temperatures. For increased temperature this effect is suppressed. The super-Poissonian noise is explained by capacitive coupling between different stacks of quantum dots.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
78
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 21 publications
(26 reference statements)
7
78
0
Order By: Relevance
“…Applying the Master equation model from [32], we find super-Poissonian noise with a characteristic two-peak structure around the location of the current resonance, see Fig. 5(c,d), which is very similar to recent experimental results [42]. Such a behavior relies on the interplay of two resonances at the same bias, see Fig.…”
Section: Current Fluctuations and Shot Noisesupporting
confidence: 71%
“…Applying the Master equation model from [32], we find super-Poissonian noise with a characteristic two-peak structure around the location of the current resonance, see Fig. 5(c,d), which is very similar to recent experimental results [42]. Such a behavior relies on the interplay of two resonances at the same bias, see Fig.…”
Section: Current Fluctuations and Shot Noisesupporting
confidence: 71%
“…In our case, as the exciton decays into surface plasmon, the non-Markovian effect from the plasmon reservoir may re-excite it now and then, such that the Fano factor is enhanced. One notes that this kind of enhancement due to quantum coherence has recently been observed in the tunneling through a stack of coupled quantum dots [22] and explained theoretically [23].…”
mentioning
confidence: 99%
“…In particular, the bunching of tunneling events, observable as an increased shot noise power, can characterize the Coulomb interaction in the transport through multilevel quantum dots. [1][2][3][4][5][6][7][8] The sequence of tunneling events is correlated by the Coulomb blockade and depends on the effective tunneling rates and internal level structure, which allows for the detection of spin-dependent tunneling through quantum dots. 9 Injection of electrons from spin-polarized leads may result in a spin-dependent blockade as shown by Ciorga et al [10][11][12] The spin blockade effect 13 has been observed in the addition spectrum of a quantum dot in a magnetic field 14,15 as a modulation of the Coulomb blockade peak amplitude or in the occurrence of negative differential resistance.…”
mentioning
confidence: 99%